SELF INSTRUCTION UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA - Yuliana, Efi Eka; Purwati, Purwati; Sugiyadi, Sugiyadi (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2014)
This research aimed at finding out the to determine influence of Self-Instruction Method training to improving Self directed learning. Research carried out on a student VII SMP 13 Magelang city.This research used experimental design that was one-group pretest-posttest design. Samples to be taken as many as 10 students who have a tendency self directed learn low. Using techniques the sample purposive sampling. Data collection method in a survey self directed of learning. Analysis of data uses statistics non parametric by test wilcoxon with the help of SPSS version 20,0 for windows.The result showed that the difference in student self directed learning before and after training with the self instruction evidenced bythe score average pretest of 164,60 and post test of 177,00 having the difference average score pretest and score posttest of 12,4 with increased average 20%. The student self directed learning shows its students who were afraid wrong ask be active and confident in question.Based in can be concluded that the training use self instruction can improve student self directed learning.